Efforts of Guidance and Counseling Teachers in Reducing TikTok Addiction in Junior High School Students - Mayasari, Aigia Dwi; Darmayanti, Nefi (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This study aims to find out the efforts made by counseling guidance teachers in reducing TikTok social media addiction in students at SMPN 2 Munte. It is a research with a descriptive qualitative approach, with data collection methods in the form of observation, interviews, and documentation, and analyzed using data triangulation techniques. Based on the research that has been carried out, the results of the efforts made by counseling teachers in reducing TikTok social media addiction in students are carrying out group guidance service activities with several scheduled meetings. Besides that, counseling guidance teachers provide information services related to the negative impact of using TikTok social media. The researcher concluded that TikTok social media can cause addiction in SMPN 2 Munte students, which hurts their mental and physical health. Therefore, there needs to be teacher efforts to help reduce TikTok social media addiction in students through efforts such as education about the negative impact of TikTok addiction, developing positive activity programs, collaborating with parents, and making clear rules and disciplinary actions for students who violate the limits of TikTok use at school. With these efforts, it is hoped that students can reduce TikTok addiction and improve their mental and physical health through more beneficial